Effect of green manure, urea nitrogen and their residuals on yield of sweet pepper (Capsicum annuum L.) and on some soil properties - Mahgoub, Manal M.; Abdelmalik, Altayeb M.; Babiker, Hashim M.; Mohamed, Ahmed Eltayeb A. (Gezira Journal of Agricultural Science, 2017)
Green Manure (GM) can be defined as a type of cover crop grown primarily to add nutrients and organic matter to the soil. The main objective of this study was to investigate the effect of green manure with urea nitrogen and their residuals on growth and yield of sweet pepper and on some soil properties. This study comprised of two experiments conducted over two consecutive seasons (2009/10-2010/11) at the Experimental Farm of the Faculty of Agricultural Sciences, University of Gezira, Sudan. Green manure was applied at 0 and normal green manure (0GM, NGM), combined with N at 0, 43 and 86 kg N ha -1 . The results showed that application of green manure alone or in combination with urea nitrogen improved soil properties and hence growth and yield of sweet pepper. Combination of inorganic and organic sources of nitrogen presumably improved nitrogen mineralization and, therefore, positively affected growth and yield of the sweet pepper. Also, the residuals of green manure and urea nitrogen remaining in the second season, improved soil properties and growth and yield of sweet pepper. It was observed that the extent of improvement was more when urea nitrogen and green manure were applied in the same season. Hence, it is recommended to fertilize sweet pepper with green manure and urea for high yield and improved soil properties.